Analysis of the therapeutic efficacy of robot-assisted percutaneous screw fixation in the minimally invasive treatment of pelvic fractures - Wang, Mige; Zheng, Song; Zhang, Yushan; Lu, Jialing (Frontiers in Surgery, 2024)
Objective: To compare the therapeutic efficacy of robot-assisted and manual screw placement techniques for the treatment of pelvic fractures. Methods: This study included patients with pelvic fractures admitted to our orthopedic department between January 2020 and January 2022. They were randomly assigned to either the robot-assisted group or the control group. Various parameters, including surgical duration, intraoperative bleeding, fluoroscopy frequency, postoperative pain, length of hospitalization, postoperative hematological indices, postoperative functional scores, and postoperative complications, were compared between the two groups. Results: There were no significant differences in age, sex, body mass index, and preoperative hematological parameters between the two groups. The robot-assisted group exhibited significantly shorter surgical duration, lower fluoroscopy frequencies, lower postoperative pain scores, and shorter length of hospitalization compared to the control group. At 3 and 6 months postoperatively, patients in the robot-assisted group demonstrated significantly higher Majeed functional scores in comparison to the control group. However, there were no significant differences in Majeed scores at 12 months postoperatively. Moreover, there were no significant differences in postoperative complications between the two groups. Conclusion: Robot-assisted minimally invasive treatment of pelvic fractures using hollow screws effectively reduced surgical duration, mitigated intraoperative bleeding and postoperative pain, shortened hospital stays, and promoted faster functional recovery.